Trade in environmental services: opportunities and constraints - Aparna Sawhney; Rupa Chanda (Indian Council for Research on International Economic Relations (ICRIER), 2003)
The environmental services sector has been growing rapidly during the last two decades. Moreover, privatization and increasing outward-orientation of environmental services during the 1990s has made this sector an important service sector for negotiations under the new round of GATS.This study explores the nature and structure of the environmental services sector, both globally and in India, with particular focus on recent trends such as privatization and foreign investment in this sector. It also discusses issues of classification and definition which have occupied centre stage in the multilateral negotiations in this sector. The study assesses the implications of liberalizing environmental services in India, taking into account the country's strengths, weaknesses, and interests in this sector. Based on this assessment, it suggests a negotiating strategy for India in environmental services in the ongoing GATS 2000 negotiations. Given the special features of this sector, the study also suggests domestic reforms and regulations to ensure equity and sustainability along with economic efficiency in the provision of environmental services in India.
Keywords: 330